An empirical analysis on habit formation of consumption with discount recursive least squares method. (17th February 2018) - Jiang, Shi; Shi, Jian-Fei
Abstract: This paper tests for the presence of habit formation using household monthly data converted from annual observations 1992-2014 of Chinese rural residents from China Statistical Yearbooks with discount recursive least squares method which can clearly examine the procedure of habit formation. The results yield evidence of habit for rural residents and show that the uncertainties probably trigger the changing of habit. And stabling policies and reducing incomes gap will be helpful to decrease the strength of habit formation and promote the growth of consumption.